2010
DOI: 10.1111/j.1442-9993.2010.02213.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat-dependent population regulation in an irrupting population of long-nosed bandicoots (Perameles nasuta)

Abstract: We used isodars to analyse habitat-dependent population regulation by long-nosed bandicoots Perameles nasuta during an irruption and subsequent population crash in three habitats (heath, woodland and forest) at Booderee National Park, south-eastern Australia. Specifically, we aimed to see whether patterns of habitatdependent population regulation matched a priori estimates of quantitative and qualitative differences between habitats. We also tested if habitat preference changed between the increasing and decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
12
1
Order By: Relevance
“…Since 1999, Booderee National Park (BNP) on the south-east coast of Australia, has maintained an intensive fox control program that has resulted in the increase in abundance of a number of native mammal species [31], [32]. There has been an increase in the abundance of macropods of approximately 10 fold between 2003 and 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1999, Booderee National Park (BNP) on the south-east coast of Australia, has maintained an intensive fox control program that has resulted in the increase in abundance of a number of native mammal species [31], [32]. There has been an increase in the abundance of macropods of approximately 10 fold between 2003 and 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these managers have lead-authored or coauthored a number of scientific articles based, in part, on the monitoring data gathered at BNP (e.g. Lindenmayer et al 2008aLindenmayer et al , 2009Dexter et al 2011Dexter et al , 2012MacGregor et al 2013). Moreover, Park staff are on the supervisory panel of several postgraduate students working on key projects within BNP to ensure these studies are relevant to management (sensu Russell-Smith et al 2003) as well as scientifically robust.…”
Section: Discussionmentioning
confidence: 99%
“…Lindenmayer et al 2008a), although, the latter species has exhibited major interannual fluctuations in abundance(Dexter et al 2011; C. MacGregor, D. Lindenmayer and J. Wood, unpublished data).…”
mentioning
confidence: 98%
“…A.2). In addition, Dexter et al (2011) used vegetation structure data 425 collected by Lindenmayer et al (2008) at BNP to provide an index of the relative protection from 426 predation afforded by each habitat for the long nosed bandicoot (a species with comparable dietary 427 requirements and predation vulnerability as the southern brown bandicoot). They found that heath 428 provided the densest understorey and thus the best protection from predators, followed by 429 woodland then forest.…”
Section: Is Conspecific Attraction or Repulsion Acting To Influence Dmentioning
confidence: 99%